PENGARUH SISTEM INFORMASI AKUNTANSI, MOTIVASI KERJA DAN KAPASITAS SUMBER DAYA MANUSIA TERHADAP KINERJA KARYAWAN PADA CV. INAURA ANUGERAH - Nurul Khoiriyah; Badrus Zaman; Andy Kurniawan (Jurnal Ilmiah Akuntansi, 2025)
Companies are required to enhance efficiency and competitiveness amid rapid technological advancements and intense business competition. Employee performance is a strategic factor that significantly determines a company’s success. This study aims to examine the influence of the accounting information system (AIS), work motivation, and human resource (HR) capacity on employee performance at CV Inaura Anugerah. The research applies a quantitative approach using survey techniques and multiple linear regression analysis via SPSS. The sample consists of 54 employees directly involved in operating the AIS, selected through purposive sampling.The t-test results show that AIS (sig. 0.000) and work motivation (sig. 0.016) have a significant effect on performance, while HR capacity (sig. 0.155) is not significant. The F-test result (sig. 0.000) indicates that the three variables simultaneously affect performance. The coefficient of determination (R²) of 0.398 reveals that 39.8% of the variation in employee performance can be explained by these variables. The research instruments are also proven to be valid and reliable.These findings highlight that effective implementation of accounting technology and strong work motivation play a vital role in improving employee performance. Therefore, it is recommended that the company enhance AIS integration and strengthen a structured motivation system to support sustainable performance improvement